Fronto-striato network function is reduced in major depressive disorder - Kijima, Reoto; Watanabe, Keita; Okamoto, Naomichi; Ikenouchi, Atsuko; Tesen, Hirofumi; Kakeda, Shingo; Yoshimura, Reiji (Frontiers in Psychiatry, 2024)
Various pathological mechanisms are implicated in major depressive disorder (MDD), including the reward system. The human brain is equipped with a reward system that is involved in aspects such as motivation, pleasure, and learning. Several studies including a meta-analysis have been reported on the reward system network and MDD. However, to our knowledge, no studies have examined the relationship between the reward system network of drug-naïve, first-episode MDD patients and the detailed symptoms of MDD or age. The fronto-striato network (FSN) is closely related to the reward system network. The present study primarily aimed to elucidate this point. Methods: A total of 89 drug-naïve first-episode MDD patients and 82 healthy controls (HCs) patients were enrolled in the study. The correlation between the FSN and age and the interaction between age and illness in the FSN were investigated in 75 patients in the MDD group and 79 patients in the HC group with available information on the FSN and age. In addition, the association between the FSN and the total scores on the 17-item Hamilton Rating Scale for Depression (HAMD-17) and scores in each symptom item was analyzed in 76 MDD subjects with information on the FSN and HAMD-17. The significance of each result was evaluated according to a p-value of <0.05. Results: Age was inversely correlated with the FSN (p=2.14e-11) in the HC group but not in the MDD group (p=0.79). FSN varied with the presence of MDD and with age, particularly showing an interaction with MDD and age (p=1.04e-08). Specifically, age and the presence or absence of MDD each affected FSN, but the effect of age on FSN changed in the presence of depression. FSN did not correlate with total HAMD-17 scores or scores in each item. Discussion: The reward system may be dysfunctional in patients with MDD. In addition, the effect could be greater in younger patients. Careful consideration should be given to age and its association with the severity of MDD. Conclusion: The reward system function is decreased in MDD patients, and this decrease may be more pronounced in younger patients, although further research is still needed.